2019
DOI: 10.3389/fendo.2019.00109
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism in Children: When a Replacement Hormonal Treatment Might Be Advisable

Abstract: Aim of this mini review was to analyze the main variables which should be taken into account when the decision regarding a possible treatment with L-T4 has to be considered for a child with subclinical hypothyroidism (SH). The indications of periodical monitoring and vigilance have been also discussed. It was inferred that therapy should be recommended for children with underlying Hashimoto's thyroiditis and progressive deterioration of thyroid status over time, particularly in the cases with goiter and hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…Thyroid function was evaluated at 8 am after an overnight fasting by measurement of basal TSH, fT3 and fT4, anti‐Tg and anti‐TPO. MSH was defined as TSH between 4.5 and 10 µU/ml and fT4 was within normal limits for age in at least two different measurements in 1 month 4 . Thyroid function tests and autoantibodies were measured using chemiluminescence (Roche Cobas E601 Immunology Analyzer, Massachusetts, USA) in the biochemistry laboratory (normal values: TSH: 0.5‐4.5 µU/mL, fT4: 0.8‐2.3 ng/dL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid function was evaluated at 8 am after an overnight fasting by measurement of basal TSH, fT3 and fT4, anti‐Tg and anti‐TPO. MSH was defined as TSH between 4.5 and 10 µU/ml and fT4 was within normal limits for age in at least two different measurements in 1 month 4 . Thyroid function tests and autoantibodies were measured using chemiluminescence (Roche Cobas E601 Immunology Analyzer, Massachusetts, USA) in the biochemistry laboratory (normal values: TSH: 0.5‐4.5 µU/mL, fT4: 0.8‐2.3 ng/dL).…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of SH in childhood is lower than 2%. SH has been accepted as a benign and remitting condition, with a low risk to progress to overt hypothyroidism, especially in children with idiopathic and MSH 4 . The clinical presentation of the children with SH may vary from no clinical symptoms to a clear picture of thyroid impairment 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these mechanisms, however, explains the thyroid dysfunction completely and hence the clinical implications remain non-absolute and specific therapy with levothyroxine is controversial [3,4]. Mild SCH, unless associated with Hashimoto's thyroiditis, is frequently considered benign in pediatric population [6,7] and therapy is recommended only if the thyroid stimulating hormone (TSH) remains consistently elevated [8][9][10]. Nevertheless, several recent studies have identified IsHT as an important risk factor for the development and progression of cardiovascular disease and nonalcoholic fatty liver disease (NAFLD) in obese children and adolescents [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with levothyroxine was initiated in all patients who presented TSH ≥10μUI/mL or TSH 5-10μUI/ mL and positive TPOAb/TgAb (G3). The dilemma arises in deciding whether patients with maintained mildly elevated TSH (G2) should be treated or not with levothyroxine and what benefits it can bring against possible consequences of SH, since good-quality studies examining the effect of treatment of SH in children are lacking [9,[24][25][26]. In our case, no patients were treated since none presented associated symptoms or alterations that could be related to it.…”
Section: Discussionmentioning
confidence: 99%